Conduta e Resultados no Tratamento do Câncer da Bexiga - Vianna, João B. (2023)
In the first part of the paper the author describes his actual conduct in the treatment of câncer of the bladder. It is based on the study of a total of 105 cases operated by from 1947 to 1966. Great Importance is given to the T.N.M. classiflcation not only as a mean of chosing the proper treatment but also regardind prognosis. In the second part of the paper the results of the first 67 cases treated from 1947 to 1962 are given. The treatment given to this first group was not exactly the same as is now recomended by the author. The 1,3 and 5 years survival of each of the stages T-1, T-2, T-3 and T-4 is given and finally the result of the totality of The 67 cases independente of staging. Results are also given regarding the different types of operation (total cystectomy, partial cystectomy etc.) and also operative mortality. Unfortunatly 29 of the 67 patients were of stage T-4 and therefore had no possibility of the benefit of a 5 years survival. This was one of the main facts of the poor results of treatment. If in the future such advanced cases could be eliminated by early detection results should certalnly improve.